Repeated Elevation of the Anterolateral Thigh Flap for Lower Extremity Orthopedic Trauma Does Not Affect Flap Viability - Kotick, James D.; Mitchell, William; Bayouth, Lilly; Klein, Richard; Lee, Ken (Journal of Reconstructive Microsurgery, 2016)
Background The anterolateral thigh (ALT) flap has a key role regarding limb salvage and has facilitated the preservation of function and esthetics in lower extremity reconstruction. The purpose of this study is to review the advantages of the ALT flap when used early in the reconstruction of the trauma patient; specifically, its long-term viability when ALT flap reconstruction is followed by recurrent flap elevation performed to allow a variety of sequential orthopedic operations including washout, antimicrobial disc placement, and reinstrumentation.Methods A retrospective analysis was performed to review all ALT flaps performed by the authors from January 2009 to October 2012 at the Orlando Regional Medical Center. A total of 69 patients with an average age of 38 years were included in the study leading to a total of 69 ALT flaps indicated for traumatic orthopedic wounds. Out of these, 29 flaps were elevated at least once leading to a total of 49 flap elevations.Results The median number of days to flap elevation was 117 with a minimum of 1 day and a maximum of 540 days. A total of 42% flaps were elevated at least once after initial placement for reinstrumentation, washout, or antibiotic disk placement. Overall, 52% of the flaps were lifted once, 34% were lifted twice, and 14% were lifted more than thrice. There is no statistically significant difference in the complication rate between elevating the flap compared with primary ALT placement.Conclusion We conclude, therefore, there is no elevated risk to long-term viability by elevating the ALT flap. This combined with the ease of elevation makes it a safe procedure to be performed as needed for access to the deep tissues.
Keywords: ALT; flap elevation; lower extremity trauma